Integrated knowledge, innovation and technology cluster as a self-regulating complex system - Rutkauskas, Aleksandras Vytautas; Račinskaja, Irena; Kvietkauskienė, Alina (Business, Management and Economics Engineering, 2013)
Current scientific literature aims for adequate understanding of the process for integration of knowledge, innovation and technology in various areas of human activity. This would materialise the hope that integrated knowledge, innovation and technology clusters could become a full-fledged resource in responding to the current and future local and global challenges of sustainable development.